AYAT AL-QUR’AN TENTANG POTENSI MANUSIA - Sari, Fatika; Badrah, Neng; Muslimin, Muslimin (Jurnal Bilqolam Pendidikan Islam, 2020)
The potential of the human self as a whole is the whole body or human body as a perfect system when compared to a perfect system and the most perfect when compared to other systems of God's creatures, such as animals, angels, jinn, devils, and demons. When identified, the potentials that already exist in humans are the mind, heart, and senses. Every thinker and expert working in a particular field needs his or her role of thought to study these human problems and concepts. Another view is that in religion or theology, human concepts have also been studied and given certain explanations. Theologians claim that humans are God's creations and must obey God's rules. Humans obey Sunnatullah. When doing something and behaving, humans must be responsible for the behavior.